Use of Kelvin probe force microscopy to achieve a locally and time‐resolved analysis of the photovoltage generated in dye‐sensitized ZnO electrodes. Issue 9 (4th July 2014) - Beu, Max; Klinkmüller, Kathleen; Schlettwein, Derck
<x xml:space="preserve">Abstract</x> Kelvin probe force microscopy at air in the dark and under illumination by visible light was performed for electrodeposited porous ZnO films, which were sensitized by the indoline dye D149. A contact potential difference was measured that confirmed electron injection into the semiconductor matrix and their subsequent stabilization in trap states. A locally widely homogenous signal was observed speaking in favor of a well‐crystallized sample. The rise and decay times of the photovoltage in the ms to s timescale could be analyzed by use of individual scan lines or scanned images, respectively. The results are discussed in the context of recent pump–probe spectroscopy results as well as such from photoelectrochemical experiments with such electrodes and implications will be deduced for their use in dye‐sensitized solar cells.